Unsaturated fatty acid salts remove biofilms on dentures - Teruyuki Hara (Nature Portfolio, 2021)
Abstract Candidiasis-causing Candida sp. forms biofilms with various oral bacteria in the dentures of the elderly, making it harder to kill and remove the microorganism due to the extracellular polymeric substances. We found that biofilms on dentures can effectively be removed by immersion in an unsaturated fatty acid salt solution. Using optical coherence tomography to observe the progression of biofilm removal by the fatty acid salt solution, we were able to determine that the removal was accompanied by the production of gaps at the interface between the biofilm and denture resin. Furthermore, microstructural electron microscopy observations and time-of-flight secondary ion mass spectrometry elucidated the site of action, revealing that localization of the fatty acid salt at the biofilm/denture-resin interface is an important factor.